Ultrathin Co films with Pt and Au covers—magnetic and structural properties driven by Ga+ ion irradiation - P Mazalski; L Ohnoutek; I Sveklo; L Beran; Z Kurant; W Powroźnik; A Wawro; M O Liedke; M Butterling; A Wagner; J Fassbender; J Hamrle; et al. (New Journal of Physics, 2021)
The X /Co 3 nm/ Y (where X , Y = Au, Pt) trilayers with as deposited in-plane magnetization alignment were irradiated with 30 keV Ga ^+ ions in the wide range of ion fluence. The samples were investigated by means of complementary techniques: magneto-optical magnetometry and spectroscopy (in the photon energy range from 1.2 eV to 4.5 eV), magnetic force microscopy, positron annihilation spectroscopy, x-ray diffraction and reflectivity. Difference in miscibility of interface atoms is clearly manifested in various intermixing extent at Co/Pt and Co/Au interfaces and consequently in magnetic properties of the irradiated trilayers. Low irradiation fluence (∼10 ^14 ions cm ^−2 ) leads to ∼1 nm interfaces broadening without visible surface etching for all samples, which is related with a distinct drop of magnetic anisotropy. However, the high irradiation fluence (∼5 × 10 ^15 ions cm ^−2 ) results in enhanced interface broadening and significant surface etching (∼5 nm) partially removing also Co atoms. Tensile strains (up to 0.5%) were developed in the cover layers. The tensile strain, layers intermixing and the creation of Co–Pt(Au) alloys with different composition formed by irradiation are correlated with the increase of magnetic anisotropy. Moreover it was observed that substitution of Au instead of Pt (as a cap or buffer layer) results in substantial increase of perpendicular magnetic anisotropy. Maximal increase of magnetooptical parameters was observed for Pt/Co/Pt layer. Irradiation induced changes of concentration profiles are revealed using magnetooptical spectra, x-ray reflectivity spectra and simulations with use of binary collision approximation.